A Conceptual Framework in the Formation of Young Entrepreneurs in Indonesia - Rahmatiah Rahmatiah; Dondick Wicaksono Wiroto; Hapsawati Taan (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2017)
This article is an initial step to reach a conceptual understanding on young entrepreneurs in sociological studies. Many studies pertaining to entrepreneurship have been found in various discipline of studies, however, nothing of note has been found particularly in connection to the concept of youth. The current reality in Indonesia precisely exhibits multiple entrepreneurship activities targeting young people as organizers and participants. The identity of entrepreneur is constructed by tracing and researching the variety of important concepts observed in various literature (written by economy, sociology, and entrepreneurship experts) concerning entrepreneur action. Entrepreneur identity has 4 dimensions: triggering event, innovation, action strategy of start-up arrangement (as stated in the business plan/model), and entrepreneurship implementation. Entrepreneur identity will be discussed by using multiple data obtained from YouTube in the form of speeches, lectures, and interviews of young entrepreneurs until an understanding is ultimately acquired regarding the identity of young entrepreneurs’ base of action by analyzing their emphasis on what they do as entrepreneurs. The discussion develops further as the identity touches on a more complex social context: social welfare, hence, young entrepreneurs also have the identity of young entrepreneurs’ social movement comprising of three phases: initiation, strategic, and control.